Hubungan Pengetahuan dan Pekerjaan Dengan Pemberian ASI Eksklusif Di Wilayah Kerja Puskesmas Martapura I Tahun 2024 - Fatimah, Siti; Hipni, Rubiati; Januarsih, Januarsih; Maslani, Noorhayati (JURNAL KEBIDANAN BESTARI, 2024)
Exclusive breastfeeding is giving breast milk to babies, without any other liquids or solids being given, even water, except for drops/syrup solutions of vitamins, minerals or medicines, exclusive breastfeeding is recommended until the child is 6 months old. To determine the factors associated with exclusive breastfeeding for babies aged 6-12 months in the Martapura I Community Health Center Work Area in 2024. Quantitative research type with a cross sectional design. A sample of 79 mothers who had babies aged 6-12 months used purposive sampling according to the researchers' criteria. The Independent Variables are Knowledge, Employment, Husband's Support, and Local Cultural Customs, while the Dependent Variable on Breastfeeding is data collection carried out by distributing questionnaires and conducting interviews with mothers who have babies aged 6-12 which contains information about the identity and knowledge of the respondents. The type of data in this research is nominal, which is analyzed through computerization. The results of the study showed that there was a relationship in all variables with exclusive breastfeeding. There were 79 samples, there were 20 (25.3%) respondents who succeeded in giving exclusive breast milk to their babies and 59 (74.7%) respondents who did not succeeded in giving exclusive breast milk to their babies. There is a relationship between Knowledge P value = 0.006, Occupation and P value = 0.001 with exclusive breastfeeding.Keywords: Exclusive breastfeeding, knowledge, work